Using the Greek goddesses to create a well-lived life for women - Beck, Martha C.; Lindsey, B. K. (Newcastle upon Tyne, UK : Cambridge Scholars Publishing, 2018)
This book brings to life the meaning of the stories of the seven goddesses of Greek mythology. Each goddess represents a sacred calling, a way of life whose goal is to live for the sake of something greater than oneself. Athena is the goddess of wisdom and justice; Artemis is the woods woman who protects the natural world; Demeter is the goddess of the fertility of the earth and the birth and nurturing of children; Hera is the wife of Zeus, the king, who dedicates her life to creating a high quality of public life through nurturing various community activities; Aphrodite is the goddess of creativity; Persephone is the victim who was raped by Hades and abducted to the underworld where she punishes those who victimized others while alive; and Hestia is the contemplative, she who reflects upon human affairs and sees how all the parts fit a larger whole. The book will allow readers to recognize themselves and their own sacred passions in these stories. Once recognized, women can educate themselves and each other. They can use the wisdom represented in Greek mythology to create meaningful and complete lives in the context of a culture that is still dominated by men and their passions. In this way, women will be liberated to do everything they can to leave a better world behind for their children, grandchildren and future generations.
Acknowledgements -- Introduction -- Chapter one. The value of myth in a post-modern world -- Chapter two. Eros and Psyche -- Chapter three. Psyche's four tasks -- Chapter four. Artemis: goddess of the hunt and moon, competitor and sister -- Chapter five. Artemis: goddess of the hunt and moon, competitor and sister -- Chapter six. Athena: goddess of wisdom and crafts, strategist and father's daughter -- Chapter seven. Athena: goddess of wisdom and crafts, strategist and father's daughter -- Chapter eight. Aphrodite: goddess of love and beauty, creative woman and lover -- Chapter nine. Aphrodite: goddess of love and beauty, creative woman and lover -- Chapter ten. Hera: goddess of marriage, commitment maker and wife -- Chapter eleven. Hera: goddess of marriage, commitment maker and wife -- Chapter twelve. Demeter: Goddess of grain, nurturer and mother -- Chapter thirteen. Demeter: goddess of grain, nurturer and mother -- Chapter fourteen. Persephone: the maiden and queen of the underworld, receptive woman and mother's daughter -- Chapter fifteen. Persephone: the maiden and queen of the underworld, receptive woman and mother's daughter -- Chapter sixteen: Hestia: goddess of the hearth and temple, wise woman and maiden aunt -- Chapter seventeen. Hestia: goddess of the hearth and temple, wise woman and maiden aunt -- Chapter eighteen. Conclusion: love story -- Bibliography.
Incluye referencias bibliográficas (páginas 265-277).
Descripción basada en metadatos suministrados por el editor y otras fuentes.
Recurso electrónico. Santa Fe, Arg.: elibro, 2020. Disponible vía World Wide Web. El acceso puede estar limitado para las bibliotecas afiliadas a elibro.
Keywords: Women -- Psychology; Women -- Conduct of life; Goddesses, Greek; Libros electrónicos.